2009
DOI: 10.1111/j.1747-0765.2009.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saline and alkaline stresses on the germination, growth, photosynthesis, ionic balance and anti-oxidant system in an alkali-tolerant leguminous forageLathyrus quinquenervius

Abstract: We compared the effects of saline stress (9:1 molar ratio of NaCl : Na 2 SO 4 , pH 6.44-6.65) and alkaline stress (9:1 molar ratio of NaHCO 3 : Na 2 CO 3 , pH 8.71-8.89) on the germination, growth, photosynthesis, ionic balance and activity of anti-oxidant enzymes of Lathyrus quinquenervius to elucidate the physiological adaptive mechanism of plants to alkaline stress (high pH). The results showed that, at a low stress intensity, the effects of saline stress and alkaline stress on L. quinquenervius were simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 33 publications
3
75
0
Order By: Relevance
“…1b) contents. It was shown that NaCl and Cd bring ionic toxicity by elevated levels of Na + [28][29][30] and Cd 2+ [32][33] in plant tissues, which disturbs nutrient uptake and stomatal opening, inhibits some of the enzymes of the Calvin cycle, and affects plant biomass [62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b) contents. It was shown that NaCl and Cd bring ionic toxicity by elevated levels of Na + [28][29][30] and Cd 2+ [32][33] in plant tissues, which disturbs nutrient uptake and stomatal opening, inhibits some of the enzymes of the Calvin cycle, and affects plant biomass [62].…”
Section: Resultsmentioning
confidence: 99%
“…Environmental stresses such as salt [28][29][30][31] and cadmium [32][33][34][35] can also affect photosynthetic pigments and inhibit photosynthesis. It was shown that PSII efficiency depends on pigment concentration and structure [36].…”
mentioning
confidence: 99%
“…Most studies examining the effects of salinity on seed germination were carried out with individual salts, especially NaCl solution (Bliss et al, 1986;Tobe et al, 1999Tobe et al, , 2000Huang et al, 2003;Zia and Khan, 2004;Li, 2008;Qu et al, 2008;Ahmed and Khan, 2010), but little information exists concerning the effect of Ca 2+ ions on seed germination (see Shaikh et al, 2007 and references therein). Calcium has been shown to inhibit Na + uptake and thereby reduce its adverse effect on seed germination (Marcar, 1986;Rengel, 1992;Ebert et al, 2002;Bonilla et al, 2004;Yang et al, 2007;Zehra et al 2012), increase plant growth (Colmer et al, 1996;Kinraide, 1999;Tobe et al, 2003;Hirschi, 2004;Joshi et al, 2012) and alleviate the toxic effects of Na + , Mg 2+ (Tobe et al, 2002(Tobe et al, , 2004Probert, 2000;Bonilla et al, 2004;Zhang and Mu, 2009) and various sulphate salts on germination or seedling growth (Tobe et al, 2002(Tobe et al, , 2004. Alkaline salts have a more severe effect on plant growth than neutral salts (Shi and Yin, 1993;Tang and Turner, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The steady-state levels of two key enzymes in JA biosynthesis, lipoxygenase (LOX) and allene oxide synthase (AOS), and the content of JA are higher in salt-tolerant tomato cultivars9. The salt hypersensitivity of the lox3 mutant can be complemented by MeJA10 (Zhang et al, 2009). …”
Section: Introductionmentioning
confidence: 99%